The Relationship Between The Intensity of Using Tiktok Social Media on Self-Confidence in College Students - Ayu Guspita Sari; Ratna Yunita Setiyani Subardjo (Publikasi Indonesia, 2024)
This research aims to analyze the relationship between the intensity of TikTok social media use and confidence in students, to find out the increase in confidence in the intensity of TikTok social media use in students, and to find out whether the intensity of TikTok social media use decreases confidence in students. The research approach carried out is quantitative. The data collection technique in this study is a list of questions (questioner). Data was collected through a questionnaire shared with 384 active student respondents at various Indonesian universities who used TikTok social media. In this study, the results of the analysis showed a significant positive relationship between the intensity of TikTok social media use and self-confidence. So, it can be said that there is a relationship between the intensity of TikTok social media use and confidence. Thus, students who intensely use TikTok social media experience an increase in confidence and students who intensely use TikTok social media do not experience a decrease in confidence. This finding is expected to provide students with insight into the intensity of TikTok social media use and how it can affect self-confidence. Therefore, students need to use TikTok social media wisely to choose to watch positive videos in order to increase their confidence.